Fetal DNA Causes Sex-Specific Inflammation From Human Fetal Membranes - Saito Reis, Chelsea A.; Ng, Po’okela K.; Kurashima, Courtney Kehaulani; Padron, Justin; Kendal-Wright, Claire Enid (Frontiers in Physiology, 2022)
Inflammation is central to the mechanisms of parturition, but our lack of understanding of how it is controlled in normal parturition hampers our ability to understand how it may diverge resulting in preterm birth. Cell free fetal DNA is found in the amniotic fluid and it is thought to be able to activate inflammation as a danger associated molecular pattern. Although its levels increase with gestational age, its effect has not been studied on the human fetal membranes. Thus, the aim of this study was to determine if fetal DNA can trigger inflammation in the human fetal membranes and thus potentially contribute to the inflammatory load. Isolated human amniotic epithelial cells and fetal membrane explants were treated apically with fetal DNA causing the translocation of NF-KB into the nucleus of cells and throughout the cells of the explant layers with time. Fetal membrane explants were treated apically with either small or larger fragments of fetal DNA. IL-6, TNF𝛂 and GM-CSF secretion was measured by ELISA and pro-MMP2 and pro-MMP9 activity measured by zymography from apical and basal media. Increased apical IL-6 secretion and basal pro-MMP2 activity was seen with small fragments of fetal DNA. When the data was disaggregated based on fetal sex, males had significant increases in IL-6 secretion and basal increased activity in pro-MMP2 and 9, whereas females had significantly increased basal secretion of TNF𝛂. This was caused by the small fragments of fetal DNA, whereas the larger fragments did not cause any significant increases. Male fetal DNA had significantly lower percentages of methylation than females. Thus, when the cytokine and pro-MMP activity data was correlated with methylation percentage, IL-6 secretion significantly correlated negatively, whereas GM-CSF secretion positively correlated. This data supports the role of fetal DNA as an inflammatory stimulus in the FM, as measured by increased NF-𝜅B translocation, cytokine secretion and increased pro-MMP activity. However, the data also suggests that the responses are different from FM tissues of male and female fetuses, and both the fragment size and methylation status of the fetal DNA can influence the magnitude and type of molecule secreted.